2017
DOI: 10.3390/su9050703
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Consumption: A Proposed Scale for Measuring the Construct Applied to a Carsharing Setting

Abstract: In recent years, there has been a significant shift towards greater collaboration in various spheres of society, in which the creation of value from shared resources while balancing self-interest and community well-being is emphasized. Consumption has ceased to be characterized exclusively by the purchase and possession of goods; instead new collaborative initiatives represented by exchanges, loans, renting, and other forms of sharing that allow consumers access to a good or service only in the time they are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 26 publications
1
39
2
4
Order By: Relevance
“…Since collaborative consumption activities such as renting, trading and purchasing secondhand items are rather unique and different from the traditional shopping process, shoppers may view these activities as more fun and exciting for the sake of new experience.It was found that the dimension of convenience, previously recognized as one of the most significant underlying dimensions of collaborative consumption(Dall Pizzol et al, 2017;Lamberton & Rose, 2012), was not found to be a significant factor in this study. Since collaborative consumption activities such as renting, trading and purchasing secondhand items are rather unique and different from the traditional shopping process, shoppers may view these activities as more fun and exciting for the sake of new experience.It was found that the dimension of convenience, previously recognized as one of the most significant underlying dimensions of collaborative consumption(Dall Pizzol et al, 2017;Lamberton & Rose, 2012), was not found to be a significant factor in this study.…”
contrasting
confidence: 78%
See 3 more Smart Citations
“…Since collaborative consumption activities such as renting, trading and purchasing secondhand items are rather unique and different from the traditional shopping process, shoppers may view these activities as more fun and exciting for the sake of new experience.It was found that the dimension of convenience, previously recognized as one of the most significant underlying dimensions of collaborative consumption(Dall Pizzol et al, 2017;Lamberton & Rose, 2012), was not found to be a significant factor in this study. Since collaborative consumption activities such as renting, trading and purchasing secondhand items are rather unique and different from the traditional shopping process, shoppers may view these activities as more fun and exciting for the sake of new experience.It was found that the dimension of convenience, previously recognized as one of the most significant underlying dimensions of collaborative consumption(Dall Pizzol et al, 2017;Lamberton & Rose, 2012), was not found to be a significant factor in this study.…”
contrasting
confidence: 78%
“…As the literature has pointed out (Botsman & Rogers, 2010;Dall Pizzol et al, 2017;Hamari et al, 2016;Möhlmann, 2015), consumers have recognized that sharing is more environmentally friendly than constantly buying new products, leading them to try collaborative consumption as an alternative. The first identified dimension was concern-for-sustainability, which suggests that consumers who are environmentally conscious about reducing waste in society demonstrate stronger orientation towards participating in collaborative consumption.…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
See 2 more Smart Citations
“…Collaborative Consumption: A Proposed Scale for Measuring the Construct Applied to a Car-Sharing Setting [11] reports on the construction of a car-sharing scale in Brazil. Starting with 29 items, 9 items were removed because of their performance in exploratory factor analyses.…”
Section: Miscellaneous Topicsmentioning
confidence: 99%